2021
DOI: 10.1021/acs.jpclett.1c03661
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Interceded Cascading Energy Transfer and Underlying Charge Transfer in Europium-Doped CsPbCl3 Nanocrystals

Abstract: Rare-earth ion (RE3+) doping in cesium lead chloride (CsPbCl3) has unlocked novel prospects to explore changes in optical, magnetic, and charge carrier transport properties. This leads to a huge advancement in optoelectronic applications, yet deep understanding of the photophysics governing the energy transfer processes is lacking and demands vital attention. Herein, we probe into the mechanistic transfer processes from the band edge of the host (CsPbCl3) to the dopant europium ion (Eu3+) with the aid of femto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Excellent optical properties of our as-synthesized NCs are demonstrated by their sharper fwhm’s of PL bands (<22 nm), higher PLQYs (91–95%), and narrower size distributions, compared to that of conventional QDs, in good agreement with previous reports (Figure a–c). , The PL spectra of our NCs are even much sharper than that of the organic dye molecules, suggesting that our NCs have broader implication for display applications. TEM images revealed the cubical shapes of our NCs, characterized by narrow size distributions, and the respective particle sizes (edge lengths) were found to be ∼8.0 ± 0.8 nm (CsPbBr 3 ), ∼10.5 ± 1.1 nm (MAPbBr 3 ), and 10 ± 1 nm (FAPbBr 3 ) (Figure d–f). Powder X-ray diffraction (PXRD) studies further confirmed the cubic perovskite structures of all three NCs (Figure g–i).…”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Excellent optical properties of our as-synthesized NCs are demonstrated by their sharper fwhm’s of PL bands (<22 nm), higher PLQYs (91–95%), and narrower size distributions, compared to that of conventional QDs, in good agreement with previous reports (Figure a–c). , The PL spectra of our NCs are even much sharper than that of the organic dye molecules, suggesting that our NCs have broader implication for display applications. TEM images revealed the cubical shapes of our NCs, characterized by narrow size distributions, and the respective particle sizes (edge lengths) were found to be ∼8.0 ± 0.8 nm (CsPbBr 3 ), ∼10.5 ± 1.1 nm (MAPbBr 3 ), and 10 ± 1 nm (FAPbBr 3 ) (Figure d–f). Powder X-ray diffraction (PXRD) studies further confirmed the cubic perovskite structures of all three NCs (Figure g–i).…”
Section: Results and Discussionsupporting
confidence: 90%
“…34 The surface trap states of semiconductor quantum dots act as quencher sites that actively participate in the carrier trapping process at ultrafast timescales (sub ps to few ps). 53,54 The absence of ultrafast decay components unambiguously confirms that our NCs are largely defect-free, and the same has been reflected through their near-unity PLQYs (Figure 2 and Table 1).…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…11,20,32,42 A probe-induced biexciton is a product of the coulombic interaction between the hot photogenerated exciton (created by the pump pulse) as it cools to the band edges and the exciton created by the probe pulse. 11,20 In order to explain it clearly, we have added a scheme (Figure S8) representing a probe-induced biexciton in the Supporting Information. Previously, numerous reports have found a concurrent increase in biexciton PL at low temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9 Besides, CsPbCl 3 with a band gap of approximately 3 eV has been under continuous attention for its ability to emit blue light and has the potential to be doped or stacked with another complementary material to emit white light. 10,11 Apart from this, CsPbCl 3 is a promising contender in several applications, including light-emitting diodes, photodetectors, and photovoltaics. 12,13 Also, to commercialize a material as a working layer in photovoltaic devices during operation, it is exposed to extreme temperature ranges, so understanding temperature-dependent material properties is vital.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides providing stability to the perovskite structures due to the reduction in defect states, partial substitution of lead ions with a limited content of impurity metal ions (such as Cu 2 + , Zn 2 + , Eu 3 + , Yb 3 + and Mn 2 + , etc.) [77][78][79][80][81] within the perovskite lattice has been established as an effective methodology to augment the solar cell efficiency. Particularly at low photoexcited carrier densities, the presence of the trap states deeply affects the carrier cooling dynamics so, it is of profound interest to explore the effect of metal ion doping on the carrier relaxation processes at such low carrier densities (< 10 18 cm À 3 ).…”
Section: The Lattice Temperaturementioning
confidence: 99%